Oxidative balance score and the potential for suffering rheumatoid arthritis: a cross-sectional study - Zhang, Yimin; Yu, Hao; Fu, Jianfei; Zhuo, Renjie; Xu, Jin; Liu, Liya; Dai, Manyun; Li, Zhen (Frontiers in Immunology, 2024)
Objective: Our study is conducted to explore the link between the oxidative balance score (OBS) and rheumatoid arthritis (RA). Methods: 21,415 participants were included in our research from five cycles (2011-2012, 2013-2014, 2015-2016, 2017-2018, 2017-2020) of the National Health and Nutrition Examination Survey (NHANES). Twenty elements related to diets as well as lifestyles were combined to calculate OBS. The relationship between OBS and RA was assessed employing multivariable regression analysis. And further exploration was carried out through subgroup analysis, restricted cubic spline analysis and sensitivity analysis. Multiple covariates were selected to adjust the model for more robust results. Results: In our cross-sectional study, higher OBS has protective effect on the development of RA (OR = 0.98, 95% CI: 0.97 to 0.99). In contrast to individuals aged ≥60, the result is more prominent in the population aged 20-60 (OR = 0.97, 95% CI: 0.96 to 0.98). Marital status appears to introduce interference in the relationship between OBS and RA. And unmarried individuals exhibited different outcomes (OR = 1.02, 95% CI: 0.99 to 1.04) compared to others. The positive influence of OBS was more evident in patients with CKD and CVD, while it was stronger in individuals without diabetes and liver disease. Conclusion: A higher OBS correlates with the reduced odd of RA. Further studies are needed to shot more sights on improving dietary and lifestyles to gain proper OBS and explore whether OBS can be one of a measurement utilized to measure the risk of RA.